The Formation, Structure and Activity of Phytochemicals 2015
DOI: 10.1007/978-3-319-20397-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Signaling: Current Perspectives on the Roles of Salicylic Acid and Its Derivatives in Plants

Abstract: Salicylic acid (SA) is an important plant hormone with a wide range of effects on plant growth and metabolism. Plants lacking SA exhibit enhanced susceptibility to pathogens. SA plays important signaling roles in resistance against biotrophic and hemi-biotrophic phytopathogens. It is synthesized in plastids along two pathways, one involving phenylalanine ammonia lyase (PAL) and the other isochorismate synthase (ICS). In Arabidopsis , during immune response most SA is synthesized through the ICS-dependent pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 198 publications
(98 reference statements)
0
14
0
Order By: Relevance
“…Salicylic acid, as a molecule, has remarkable properties in multiple fields [18]. Independent of its rich and storied medical history and modern relationship with aspirin, salicylic acid is a common, nearly ubiquitous, phenolic secondary metabolite of plants [18,19,20]. The chemical properties of the molecule make it readily soluble inside plant tissue [20] and easily transported in its methylated form [21,22].…”
Section: Primary Effects Of Samentioning
confidence: 99%
See 1 more Smart Citation
“…Salicylic acid, as a molecule, has remarkable properties in multiple fields [18]. Independent of its rich and storied medical history and modern relationship with aspirin, salicylic acid is a common, nearly ubiquitous, phenolic secondary metabolite of plants [18,19,20]. The chemical properties of the molecule make it readily soluble inside plant tissue [20] and easily transported in its methylated form [21,22].…”
Section: Primary Effects Of Samentioning
confidence: 99%
“…Production of salicylic acid occurs in plant plastids where the end product in the shikimic acid pathway, chorismic acid can be further processed into either isochorismic acid or prephenic acid then L-phenylalanine and trans-cinnamic acid [19]. These two parallel pathways each rely on separate enzymes, isochorismate synthase (ICS) and phenylalanine ammonia lyase (PAL, responsible for conversion of L-phenylalanine to trans-cinnamic acid) respectively [19,24]. Genes responsible for production of these enzymes and their homologs were identified in several plant species [19,24].…”
Section: Primary Effects Of Samentioning
confidence: 99%
“…To unravel the underlying mechanisms accounting for the changes in SA and JA contents in the two varieties after inoculation, qRT-PCR was used to assess the expression levels of SA and JA synthesis-related genes. SA is synthesized through either the isochorismate synthase (ICS) or the PAL catalyzed step (Kumar et al, 2015). qRT-PCR results showed that the transcript levels of ICS, PAL1-1 and PAL1-2 were all upregulated in Wanjincheng orange (S) and Jindan (R) after Xcc inoculation.…”
Section: Sa Synthesis Is Upregulated More In the Resistant Citrus Whmentioning
confidence: 99%
“…SAR induction in plants is strongly linked to the synthesis of salicylic acid (SA), especially in distal tissues, in response to pathogen attack [21]. SA is a small phenolic compound that not only participates in the induction of immunity but also regulates a number of aspects of plant maturation, including thermogenesis, growth, respiration, and thermotolerance [39]. In addition to SA, jasmonic acid (JA) and ethylene (ET) also participate in plant resistance, but they are synthesized to a greater extent in response to tissue damage caused by insects and during the induction of ISR [15,40,41].…”
Section: Introductionmentioning
confidence: 99%